Low Power Consumption IoT Weather Monitoring System for Coastal Areas - Wiwi, Muhammad Hibrian; Awaluddin, Muhammad; Saharis, Risky (ILKOM Jurnal Ilmiah, 2025)
This research aims to design and develop a real-time weather monitoring system in coastal areas using weather sensors integrated with Internet of Things (IoT) technology. This system wants to provide accurate weather information that fishermen can access directly through web-based platforms or mobile devices. Fishermen can make the right and safe decisions before going to sea, improving fishing activities' safety and efficiency. How to overcome the limitations of traditional weather monitoring methods that are manual, non-real-time, and discontinuous, and how to design systems that can transmit weather data automatically and in real-time in coastal areas that are often difficult to reach by power grids and stable internet. Another essential issue formulated is how to optimize the power consumption of sensor and communication systems so that they can operate efficiently using battery power resources for an adequate period. This study confirms the importance of energy efficiency in battery-based monitoring systems, especially in sensor nodes installed in remote locations without a fixed power source. The test results show the difference between the estimated operating time based on theoretical calculations and the results of simulations or real tests in the field. In idle mode, theoretical calculations estimate the system can last up to about 12.8 hours, but actual simulations show an endurance of about 7.3 hours. Meanwhile, in active mode, the estimated calculation is around 5.5 hours, while the simulation shows a slightly longer endurance, which is about 7.2 hours.